Geometry optimization, impact of solvation on the spectral (FT-IR, UV, NMR) analysis, Quantum chemical parameters, and the bioactivity of feruloyltyramine as a potential anti-Lassa virus agent via molecular docking - Antai E. Eyo; Gulack A. Obadiah; Innocent Benjamin; Uwem O. Edet; Faith O. Akor; Elizabeth Mbim; Ani Nkang; Ibor Richard; Emmanuel Emmanuel; Oluwadamilola V. Ayoola; Godwin Joshua; Hitler Louis (Chemical Physics Impact, 2023)
The unrelenting menace of the Lassa virus, characterized by its high mortality rate and the potential for global dissemination, underscores an urgent call for its comprehensive eradication to safeguard global public health. In light of this, this research embarked on an extensive investigation of trans-N-feruloyltyramine (FLTM), a compound derived from Cissampelos pareira. This study encompassed a thorough examination of its structural characteristics, utilizing spectroscopic analyses including FT-IR, UV, and NMR, with the aim of elucidating its electronic, structural, and biological properties. Seamlessly integrating experimental and theoretical approaches at the DFT/B3LYP/def2SVP level of theory in FLTM_dmso, FLTM_gas, FLTM_H2O, and FLTM_MeOH solvation. Moreover, solvation dynamic simulation highlighted FLTM's heightened total energy and enhanced solubility across dimethyl sulfoxide (DMSO), water (H2O), and methanol (MeOH) phases, signifying efficient distribution to target sites and emphasizing its potential as a drug candidate. Conversely, FLTM_gas exhibited lower total energy. Electronic properties further elucidated FLTM's reactivity and kinetic stability, with FLTM_DMSO displaying the lowest energy gap among solvents and corresponding values of 1.4168, 4.2159, 4.2175, and 4.2749 eV. These findings mirrored the compound's higher reactivity and lower kinetic stability compared to FLTM_H2O, FLTM_gas, and FLTM_MeOH, aligning with principles of chemical hardness and softness. Results of the molecular docking introduced FLTM as a potential Lassa fever treatment candidate, surpassing Ribavirin in binding affinities with Lassa virus target receptors. FLTM exhibited binding energies of -6.5 kcal/mol, -7.2 kcal/mol, and -8.2 kcal/mol in 7UOT, 3MX5, and 3MX2, respectively, establishing interactions with crucial amino acid residues. These findings strongly advocate for FLTM's efficacy, meriting further in vitro and in vivo investigations for clinical validation.